Risk Factors for High-Arched Palate and Posterior Crossbite at the Age of 5 in Children Born Very Preterm: EPIPAGE-2 Cohort Study - Herrera, Sandra; Pierrat, Véronique; Kaminski, Monique; Benhammou, Valérie; Marchand-Martin, Laetitia; Morgan, Andrei S.; Le Norcy, Elvire; Ancel, Pierre-Yves; Germa, Alice (Frontiers in Pediatrics, 2022)
Introduction: Children born very preterm have an immature sucking reflex at birth and are exposed to neonatal care that can impede proper palate growth. Objectives: We aimed to describe the frequency of high-arched palate and posterior crossbite at age 5 in children born very preterm and to identify their respective risk factors. Methods: Our study was based on data from EPIPAGE-2, a French national prospective cohort study, and included 2594 children born between 24 and 31 weeks’ gestation. Outcomes were high-arched palate and posterior crossbite. Multivariable models estimated by generalized estimation equations with multiple imputation were used to study the association between the potential risk factors studied and each outcome. Results: Overall, 8% of children born very preterm had a high-arched palate and 15% posterior crossbite. The odds of high-arched palate were increased for children with low gestational age (24-29 vs 30-31 weeks’ gestation) (adjusted odds ratio [aOR] 1.76, 95% confidence interval [CI] 1.17, 2.66), thumb-sucking habits at age 2 (aOR 1.53, 95% CI 1.03, 2.28) and cerebral palsy (aOR 2.18, 95% CI 1.28, 3.69). The odds of posterior crossbite were increased for children with pacifier-sucking habits at age 2 (aOR 1.75, 95% CI 1.30, 2.36). Conclusions: Among very preterm children, low gestational age and cerebral palsy are specific risks factors for a high-arched palate. High-arched palate and posterior crossbite share non-nutritive sucking habits as a common risk factor. The oro-facial growth of these children should be monitored.